Real-time operating systems. Book 2, The practice / Jim Cooling - Cooling, Jim
There’s something really satisfying about turning theory into practice, bringing with it a great feeling of accomplishment. Moreover it usually deepens and solidifies your understanding of the theoretical aspects of the subject, while at the same time eliminating misconceptions and misunderstandings. So it’s not surprising that the the fundamental philosophy of this book is that ‘theory is best understood by putting it into practice’.